Figurative Language and Its Meaning Found in The Novel “It Starts with Us” - Maria Osmunda Eawea Monny (Journal on Education, 2023)
Figurative language is one of the literary devices used to enrich the meaning of literature work. The research problem of this research is to find the figurative language and its meaning in the novel “It Starts with Us”. This is qualitative research and used literary study. The data collection is taken from the novel “It Starts with Us” by Collen Roover, published in 2022. The data shows that there were five kinds of figurative language simile, metaphor, personification, hyperbole, and repetition. Out of 86 data; 76 data (86%) were simile that consisted of using “like” 65 data (75,5%), using “as” 6 data (6,9%), and using “as…as” 3 data (3,4%). Data figurative language on metaphor and hyperbole were 4 each (4,65%). The last data were personification and repetition which with 2 data each (2,32%). It can be concluded that the novelist emphasized the expressions of metaphor to compare the situation and emotions in the story of the novel.